Implementasi Prinsip Ekonomi Syariah dalam Manajemen Keuangan di BMT UGT Nusantara - Ahmad Samsudin; Nurul Setianingrum (GLOBAL SCIENTS PUBLISHER, 2025)
This study discusses the implementation of Islamic economic principles in financial management at Baitul Maal wa Tamwil (BMT) UGT Nusantara. In the era of globalization, Islamic financial institutions are becoming increasingly relevant, particularly in providing ethical and sustainable financial access. This research aims to explore the application of Islamic principles such as justice, transparency, and the prohibition of usury, as well as the challenges faced in financial management practices. The research employs a qualitative approach with an in-depth literature analysis. The findings indicate that BMT UGT Nusantara has effectively implemented Islamic principles, although it still faces challenges related to customer understanding and frequently changing regulations. Additionally, BMT plays a significant role in empowering the community through training and mentoring programs aimed at enhancing the skills and capacities of its clients. This research is expected to provide significant contributions to the development of microfinance institutions in Indonesia and to increase public understanding of the importance of financial management in accordance with Islamic principles. These findings can serve as a reference for other institutions in effectively implementing Islamic principles.